Coronary artery ectasia. Its prevalence and clinical significance in 4993 patients. Issue 4 (October 1985) - Hartnell, G G; Parnell, B M; Pridie, R B
Abstract : To assess the clinical significance of coronary artery ectasia 4993 consecutive coronary arteriograms were reviewed to identify patients with this condition and to allow the assessment of their progress. Coronary ectasia was a relatively uncommon finding (overall incidence 1.4%). It was not related to the development of aortic aneurysms and did not affect the outcome, results of coronary artery surgery, or symptoms.